The Tadpoles and Advertisement Call of Trachycephalus imitatrix and T. dibernardoi (Anura: Hylidae) - Provete, Diogo B.; Garey, Michel V.; Picheli, Katiuce O. [UNESP]; Mello, Caio Marinho; Silva Gonçalves, Darlene Da; Conte, Carlos Eduardo; Rossa-Feres, Denise De C. [UNESP] (Society for the Study of Amphibians and Reptiles, 2021)
Herein, we describe the external larval morphology, internal oral features, and chondrocranium of Trachycephalus imitatrix and Trachycephalus dibernardoi and the advertisement call of T. imitatrix. To our knowledge, this is the first thorough description of the larval chondrocranium for the genus Trachycephalus. The tadpole of T. imitatrix is overall similar to the other congeneric species, but can be distinguished from them by the following combination of characteristics: presence of two folds in the posterior labium, clumped submarginal papillae, tail ending in a flagellum, buccal roof arena lacking papillae, and seven postnarial papillae. The tadpole of T. dibernardoi can be distinguished from its congeners by the following combination of characteristics: snout rounded in lateral view, absence of interruption in teeth rows, uniseriate and alternated row of marginal papillae, two pairs of infralabial papillae, and absence of projection of the dorsal velum. The advertisement call of T. imitatrix is very similar to that of Trachycephalus nigromaculatus, but can be distinguished from it by its lower dominant frequency. Additionally, both spectral and temporal features of the call can distinguish T. imitatrix from other congeneric species. Our results help understand the differentiation of larval and acoustical characteristics within the genus Trachycephalus.